Synthesis, phase composition, Mossbauer and magnetic characterization of iron oxide nanoparticles - Sarveena (2016)
The present work describes the synthesis of iron oxide nanoparticles by thermal decomposition of Fe-precursors in argon and vacuum environments with control over particle size distribution, phase composition and the resulting magnetic properties. The Rietveld analysis of X-ray diffraction data revealed the crystallinity as well the single-phase of g-Fe2O3 nanoparticles prepared under vacuum, whereas the argon environment leads to the formation of multi-phase composition of g-Fe2O3/Fe3O4 (90%) and wustite (10%). Synchrotron X-ray absorption near edge structure (XANES) indicates that the predominant phase in both the samples is g-Fe2O3, which is subsequently verified from the Mo¨ssbauerspectra. DC magnetic measurements indicate behavior typical of a superparamagnetic system validated by Mo¨ssbauer analysis. However, further investigation of ac susceptibility by typical Ne´el?Arrhenius andVogel Fulcher magnetic models suggests an influence of interparticle interactions on the overall magnetic behavior of the system.